2020
DOI: 10.1371/journal.pone.0226483
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and behavioral change during epidemics: Comparing models of individual and collective learning

Abstract: Modern societies are exposed to a myriad of risks ranging from disease to natural hazards and technological disruptions. Exploring how the awareness of risk spreads and how it triggers a diffusion of coping strategies is prominent in the research agenda of various domains. It requires a deep understanding of how individuals perceive risks and communicate about the effectiveness of protective measures, highlighting learning and social interaction as the core mechanisms driving such processes. Methodological app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 40 publications
8
74
1
1
Order By: Relevance
“…A review of the application of AI for such a prediction is reported in [17]. A collective learning based approach [18] is proposed to identify individual risk. In the last few years, machine learning analysis was used to predict epidemiological characteristics of the Ebola virus (EBOV) outbreak in West Africa [19] and the risk of Nipah virus [20].…”
Section: Related Workmentioning
confidence: 99%
“…A review of the application of AI for such a prediction is reported in [17]. A collective learning based approach [18] is proposed to identify individual risk. In the last few years, machine learning analysis was used to predict epidemiological characteristics of the Ebola virus (EBOV) outbreak in West Africa [19] and the risk of Nipah virus [20].…”
Section: Related Workmentioning
confidence: 99%
“…A nice review of the AI application on such a prediction is reported in [12]. A collective learning based approach [13] is proposed to identify individual risk. In the last few years, machine learning analysis is used to predict epidemiological characteristics of the Ebola virus(EBOV) outbreak in West Africa [14] and such analysis is also used in [15] to assess the risk of Nipah virus.…”
Section: Related Workmentioning
confidence: 99%
“…Artificial Intelligence tools are proposed for predicting outbreak for some diseases (Philemon et al, 2019;Abdulkareem et al, 2020). For example, Diarrhea outbreak (Machado et al, 2019) and cardiovascular diseases (Mezzatesta et al, 2019;Jhuo et al, 2019).…”
Section: Related Workmentioning
confidence: 99%